A Study On Employees Perception Towards The Promotion Policy Based On Monthly Income, Experience And Marital In Tamil Nadu State Transport Corporation With Reference To Tirunelveli Division (International Journal of Food and Nutritional Sciences, 2022)
This study focused the perception of the employees on promotion policy in Tamil State Transport Corporation in Tirunelveli Division, with the objectives to study the promotion policy in Tamil Nadu Transport Corporation in Tirunelveli division; to analyse the respondents’ perception of promotion policy based on monthly income, experience and marital status in Tamil State Transport Corporation in Tirunelveli Division. The researcher used both primary and secondary data. The primary data were collected from a sample of 938 employees consisting of 52 administrative staff, 378 drivers, 376 conductors and 132 technical staff. The respondents from each job category were chosen using simple random procedure. The researcher has given a number of value suggestions for the improvement of promotion policy followed in Tamil State Transport Corporation in Tirunelveli Division for the benefit of the employees and the organization.